EPILEPSY: IS IT POSSIBLE TO HAVE QUALITY OF LIFE WITH EPILEPSY? - Daniela Rodrigues Cunha, Claudia; D’avila Rocha Batista, Leide; Costa Valbão Freire, Sigrid (Health and Society, 2023)
Epilepsy is a chronic neurological disorder characterized by the recurrent and unpredictable occurrence of seizures. Seizures are episodes of abnormal electrical activity in the brain that can affect different areas and functions of the body. This disordered electrical activity can lead to symptoms such as involuntary movements, loss of consciousness, strange sensations, sensory changes, unusual behavior or confusion. Understanding the different types of seizures, potential triggers, and how to administer first aid during a seizure can help reduce anxiety and increase feelings of control. In this way, the objective of this study is to understand the ways of living and dealing with epilepsy in favor of a better life. Maintaining a healthy lifestyle can help improve the quality of life for people with epilepsy, including hours of sleep, diet and regular physical activity. The methodology was a bibliographic review, concluding that it is possible to live with seizures as long as there are preventive and adequate treatment measures, aware that each case of epilepsy is unique, and the treatment and management of the condition must be personalized to meet individual needs. Emotional support, adherence to prescribed treatment, self-management and a positive approach can help people with epilepsy achieve a good quality of life.